Motherhood Exaggerated - Hannan, Judith (Book collections on Project MUSE., 2012)
When eight-year-old Nadia cracks her jaw on a piece of Halloween candy unmasking a rare bone cancer, mother and daughter are launched on a revelatory journey of treatment, recovery and survival.